Hubungan Kelengkapan Rekam Medis Dengan Keakuratan Kode Typhoid Fever Rawat Inap Rumah Sakit Santa Elisabeth Medan - Nasipta Ginting; Pomarida Simbolon; Vivian Eliyantho Gulo (SEHATI: Jurnal Kesehatan, 2024)
The accuracy of the code is the accuracy in providing codes that are in accordance with the diagnosis of the disease and in accordance with the classification in ICD-10, which is useful to support the services and medical actions provided to patients. Completeness of medical records is the complete filling of medical records properly and correctly for medical services. The purpose of the study was to identify the relationship between the completeness of medical records and the accuracy of the typhoid fever code in hospitalization at Santa Elisabeth Hospital Medan in 2023. Analytic research design using a cross sectional approach. The population in the study were medical records of typhoid fever patients hospitalized at Santa Elisabeth Hospital Medan in 2023 as many as 214 medical records, the sample in the study was 66 medical records, the sampling technique was systematic random sampling. The instrument used was a checklist sheet. Data analysis using the Chi-square test. The results of this study obtained completeness of medical records with a complete category of 57 medical records (86.4%), the accuracy of the code with an accurate category of 51 codes (77.3%). Chi-square test results obtained p-value 0.023 (p less than 0.05) indicates that there is a significant relationship between the completeness of medical records and the accuracy of the typhoid fever code inpatient Santa Elisabeth Hospital Medan.